Dentin dysplasia type I with pyogenic granuloma in a 12-year-old girl - Nirmala SVSG; Sivakumar N; Usha K (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2009)
This paper presents a case of dentin dysplasia, a rarely reported disorder that is also associated with pyogenic granuloma in a 12-year-old girl. The case presented as excessively mobile teeth that appeared radiographically as rootless teeth and also as a soft tissue lesion in the right maxillary anterior region.